Ultrasmall targeted nanoparticles with engineered antibody fragments for imaging detection of HER2-overexpressing breast cancer. Issue 1 (December 2018) - Chen, Feng; Ma, Kai; Madajewski, Brian; Zhuang, Li; Zhang, Li; Rickert, Keith; Marelli, Marcello; Yoo, Barney; Turker, Melik; Overholtzer, Michael; Quinn, Thomas; Gonen, Mithat; et al.
Abstract Controlling the biodistribution of nanoparticles upon intravenous injection is the key to achieving target specificity. One of the impediments in nanoparticle-based tumor targeting is the inability to limit the trafficking of nanoparticles to liver and other organs leading to smaller accumulated amounts in tumor tissues, particularly via passive targeting. Here we overcome both these challenges by designing nanoparticles that combine the specificity of antibodies with favorable particle biodistribution profiles, while not exceeding the threshold for renal filtration as a combined vehicle. To that end, ultrasmall silica nanoparticles are functionalized with anti-human epidermal growth factor receptor 2 (HER2) single-chain variable fragments to exhibit high tumor-targeting efficiency and efficient renal clearance. This ultrasmall targeted nanotheranostics/nanotherapeutic platform has broad utility, both for imaging a variety of tumor tissues by suitably adopting the targeting fragment and as a potentially useful drug delivery vehicle. One of the major obstacles in nanoparticle-based therapy is to achieve tumour targeting, limiting non-specific accumulation of the nanoparticles. Here the authors propose the conjugation of anti-HER2 scFv fragments to the silica nanoparticles, increasing specificity and limiting the final size of the immunoconjugates below the renal clearance threshold.